Hysteroscopic hysteroplasty for the treatment of T-shaped uteri in women with reproductive failure - Guangping, Zhao; Li, Zhang; Shangping, Du; Tong, Zhou; Liguo, Li; Qiaoli, Tong (Frontiers in Medicine, 2023)
Objective: To evaluate the efficacy of hysteroscopic hysteroplasty in the treatment of uterine malformation complicated with primary reproductive disorders. Methods: Women with unexplained primary infertility, repeated in vitro fertilization (IVF) failure or repeated spontaneous abortion, and uterine malformations unrelated to diethylstilbestrol who visited the obstetrics and Gynecology department of our hospital from January 2019 to December 2022 were included in the prospective cohort study. The patients were confirmed by three-dimensional ultrasound and diagnostic hysteroscopy. Hysteroscopic hysteroplasty was performed using a 5 mm diameter hysteroscope and 5-FR surgical scissors, and after 3 months, palliative care was proposed for patients with unexplained infertility or repeated spontaneous abortion, and after 6 months, IVF treatment was recommended for patients with repeated in vitro fertilization (IVF) failures, with a planned minimum follow-up time of 1 year. Result: A total of 83 women were enrolled, including 33 cases of primary infertility, 29 cases of repeated spontaneous abortion, 21 cases of repeated IVF failure, and no complications occurred during hysteroscope surgery. During the follow-up period, the clinical pregnancy rate of 83 women increased to 77.1%, the live birth rate increased to 79.7%, the fetus delivered at full term accounted for 64.1%, and the cesarean section rate was 27.5%. The miscarriage rate was 9.4%. Conclusion: Hysteroscopic hysteroplasty can improve the reproductive outcomes of women with primary reproductive disorders and uterine malformations.